Analisis segementasi konsumen dalam konsumsi produk pangan bersertifikat halal pada ritel modern Yogyakarta - Tian Nur Ma’rifat; Arief Rahmawan (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2018)
Halal food is the main requirement for food consumed by consumers who are Muslim. The market opportunity for halal and good food is very wide open and promising. In preparing the halal food marketing strategy, analysis of consumer segmentation is needed as a basis in determining the target and position of halal products. Analysis of consumer segmentation is based on factors that influence consumer purchasing decisions on food products available in modern retail Yogyakarta. The method used in this study is Cluster Analysis. The sampling method used was Purposive Sampling with the number of respondents 201 respondents. The results of the study show that there are two groups of consumers, the first group that is critical and the second group that is not critical of halal status from those purchased. Therefore, efforts to increase the market share of halal certified food in DIY can be done with a strategy that focuses on factors that significantly shape consumer behavior and is aimed at groups of consumers who are critical of food security.